The Significance of Ijtihad in Resolution Syariah: Towards a Takaful Legal Framework in Malaysia - Mustafa, Aisyah; Ab Rahman, Asmak (European Journal of Islamic Finance, 2023)
Takaful businesses have to be run according to Shariah. In takaful operations, many shariah issues have arisen based on operations, activities, products, investments, etc. In Malaysia, under the Islamic Financial Service Act (IFSA 2013), takaful operators are required to form a Shariah committee to advise and resolve these Shariah issues. This study will examine the significance of ijtihad that has been done by the Shariah Advisory Council (SAC) in solving the Shariah issues faced by the industry. The study is qualitative-based research that used various documents related to takaful business in Malaysia. The study results show that the ijtihad issued by SAC influences the takaful legal framework in Malaysia, particularly when it comes to shariah issues. Other countries could learn from this to implement Islamic law in legal and regulatory frameworks, especially in the Islamic finance industry.